O Profissional de Educação Física no Sistema Único de Saúde: a pedagogia do cuidado e a promoção da saúde - Medeiros, Valeria Matos Leitão de (2009)
This study aimed to analyze the social representations of physical education professionals in the Unified Health System (SUS), some of the "pedagogy of care" such as education action toward a possible new seed promoter of health. This is a qualitative research based on the testimony of nineteen professional Fitness Project Healthy Living João Pessoa - Citizen Academy, the Municipal Health of João Pessoa. Empirical data were collected through observations and patchy semi-structured interview addressing the questions guiding this study: What is "caring" or "care" for the professional physical education? As physical education professionals care? It was also the testimonies of people involved in the project. Information was collected between January and April 2008, respecting the ethical aspects. In interpreting the data, using the analysis of content proposed by Bardin reflected the theory of social representations suggested by Durkheim and others. Social representations about what care and how care is the care referenced as a means of caring for themselves as well as the other and represent zeal, donation, satisfaction, prevention, protection, concern for community needs such as mental health , physical, and spiritual welfare, through listening, dialogue and tap the perspective of a working man that permeates the educational act, considering awareness as part of the educational process and to be valued. The discussions here also developed guidelines set out by the International Conference on Health Promotion, articulated the "policies" towards public health in recent decades also known as policies of Public Health. We believe that the professional physical education in the Unified Health System, has knowledge to contribute to the promotion of health, not in verticalized activity, but through a "pedagogy caregiver" to the exchange of knowledge from the needs and desires of other , making possible the success of health care as an ongoing and lasting change and aiming to improve the quality of life.